Pengaruh Disiplin Kerja Dan Kualitas Pelayanan Publik Terhadap Kepuasan Masyarakat Pada Kantor Kecamatan Bungah Kabupaten Gresik - Muhammad Imron Hamzah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to find out whether work discipline and quality of public services influence public satisfaction at the Bungah sub-district office, Gresik district. This research uses primary data by distributing questionnaires to all employees. The population used is people who provide services at the Bungah sub-district office. The analysis technique used is multiple linear regression analysis. The results obtained are that work discipline has a positive and significant effect on community satisfaction at the Bungah sub-district office, Gresik district. and service quality has a positive and significant effect on community satisfaction at the Bungah District office, Gresik Regency.